The inner ocean individualism and democratic culture - Kateb, George 1931- (Cornell Univ. Press, 1992)
Kateb employs the concept at individuality not only to criticize communitarianism and to define the limits of the role of the state, but also to approach global concerns involving our relation to nature. The ten essays of this book explore democratic individuality in light of such topics as the power of political institutions to accommodate and express different values, the moral distinctiveness of representative democracy, the implications of the liberal social contract, and the possibility of human extinction. Certain essays draw upon the ideas of Neitzche and Heidegger, while others turn to Emerson, Thoreau and Whitman for expressions of the potential of democratic culture today. Eloquently addressing issues at the heart of democratic life, The Inner Ocean will be of vital interest to scholars and students in American studies, political theory, and moral philosophy
Keywords: Democracia; Democratie; Démocratie; Individualisme; Demokratie; Individualism; Democracy; Individualismus